2018
DOI: 10.2337/ds17-0058
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Diabetes Knowledge, Glycemic Control, and Associated Health Conditions

Abstract: Diabetes self-management education and support is a crucial component of diabetes care. There is a considerable need for diabetes education strategies to improve self-management of diabetes and thereby improve outcomes and decrease the costs of diabetes-related care. There is also a need for efforts to ensure regular vision screenings for individuals with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 11 publications
3
14
0
Order By: Relevance
“…Therefore, level of controlling for baseline HbA 1c and other measures of diabetes severity highly depends on physicians’ characteristics 3133. As well, a patient who followed the advice of a physician regarding medication, meal plan and exercises had better control over diabetes in our population parallel with other studies 34,35. Regular monitoring of blood sugar may encourage the physician to manage and provide confidence to their patients for the better management of the glycaemic control.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Therefore, level of controlling for baseline HbA 1c and other measures of diabetes severity highly depends on physicians’ characteristics 3133. As well, a patient who followed the advice of a physician regarding medication, meal plan and exercises had better control over diabetes in our population parallel with other studies 34,35. Regular monitoring of blood sugar may encourage the physician to manage and provide confidence to their patients for the better management of the glycaemic control.…”
Section: Discussionsupporting
confidence: 52%
“…The long duration of hyperglycemia and hyperinsulinemia impairs the sensitivity and secretion of insulin, and the body becomes more resistant to insulin. Thus, this decreases the GLUT4 transportation and utilization, which results in an increment of carbohydrate in circulation, leads to its attachment to HbA 1c 2628…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Studies have shown that diabetes knowledge correlates with glycemic control so the use of a knowledge assessment tool may be useful to educators when developing individualized education plans for patients. [9][10][11][12][13] Use of a psychometrically validated multiple-choice questionnaire to guide diabetes education sessions has resulted in improvements in clinical biomarkers, receiving preventative services related to diabetes, patient satisfaction, and healthcare costs, however, this tool is not available for use by providers. [15][16][17][18] The purpose of this study was to demonstrate that use of a curriculum-specific knowledge assessment may have clinical importance in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that an increase in diabetes knowledge correlates to a decrease in fasting glucose, cholesterol, and A1C, and has shown to improve selfcare behaviors. [9][10][11][12][13] Validated diabetes knowledge scales and assessments are available for educators to utilize but they tend to measure different aspects of self-care making it challenging to determine which is most appropriate to use. 14 Other pilot programs have used a psychometrically validated tool, not yet available nationally to providers, to assess a patient's knowledge of their diabetes, lifestyle requirements, and medication-taking strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Health literacy affects people's ability to navigate the healthcare system, engage in self-care and chronicdisease management, and may, in turn, also affect the way knowledge about diabetes is understood and remembered for application at a later time (Powell, Hill & Clancy, 2007;Bains & Egede, 2011). Patients with diabetes who lack adequate health literacy and knowledge have a higher risk of poor glycaemic control and microvascular complications (Phillips, Rahman & Mattfeldt-Beman, 2018;Saeed et al, 2018).…”
Section: Introductionmentioning
confidence: 99%